Sahel, Senegal / Niger. Siedlungs- und Wirtschaftsgeschichte in der Eisenzeit und dem Frühmittelalter im Sahel Westafrikas - Magnavita, Sonja (e-Forschungsberichte des DAI, 2023)
Recent field research in Central Senegal shows that, analogue to South-West Niger, the visible wealth of some Sahelian groups during the Iron Age and early Middle Ages cannot be solely attributed to agricultural surpluses. Those investigations show that both regions imported copper alloys from northern Africa and used them for demonstrating socio-economic status. In contrast to the Niger bend, gold likewise rose to a visible status symbol in Senegal. Since the Central Senegal has no own gold deposits, a connection to distant south-eastern regions must have existed.